2015
DOI: 10.1007/s10646-015-1510-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Responses in Adult Zebrafish (Danio rerio) Exposed to Propranolol and Metoprolol

Abstract: β-adrenergic receptor blockers (β-blockers) are widely detected in the aquatic environment; however, the effects of these pharmaceuticals on aquatic organisms remain uncertain. In this study, adult zebrafish were exposed to two different β-blockers, propranolol and metoprolol, for 96 h. After exposure, the transcriptional responses of genes encoding the β-adrenergic receptor (i.e., adrb1, adrb2a, adrb2b, adrb3a and adrb3b), genes involved in detoxification and the stress response (i.e., hsp70, tap, mt1 and mt2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The presence of β-blockers has been detected in effluents at concentrations with units ranging from of ng/L to µg/L [106,107]. Similar to other pharmaceuticals, their presence in the aquatic ecosystem poses significant harm to organisms such as fish, phytoplankton and daphnia [108][109][110].…”
Section: Anxiolytics Sympatholyticsmentioning
confidence: 99%
“…The presence of β-blockers has been detected in effluents at concentrations with units ranging from of ng/L to µg/L [106,107]. Similar to other pharmaceuticals, their presence in the aquatic ecosystem poses significant harm to organisms such as fish, phytoplankton and daphnia [108][109][110].…”
Section: Anxiolytics Sympatholyticsmentioning
confidence: 99%
“…In addition, adrb2a is also known as the gene encoding the β-adrenergic receptor in zebrafish, which is localized in the brain and involved in the oxidative stress response. 45 Our previous study also found that AgNP can induce oxidative stress in zebrafish. 17 Lysophosphatidic acid (LPA) was robustly expressed in migratory neurons, which depleted neurons show impaired multipolar-to-bipolar transition.…”
Section: Discussionmentioning
confidence: 89%